2012
DOI: 10.1016/j.jff.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Magnoflorine from Tinospora cordifolia stem inhibits α-glucosidase and is antiglycemic in rats

Abstract: A B S T R A C TAntidiabetic potential of Tinospora cordifolia stem is well proven. In the course of screening of useful a-glucosidase inhibitors, we prepared alkaloid fraction (AFTC) and isolated three isoquinoline alkaloids, namely, jatrorrhizine, palmatine and magnoflorine as active candidates for a-glucosidase inhibition. The enzyme kinetics was studied using sucrose and maltose as substrates. Michaelis-Menten constant (K m ) and maximal velocity (V max ) values were estimated. A significant decrease in V m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 18 publications
2
50
1
3
Order By: Relevance
“…Hung et al (2007) also have reported that, magnoflorine played a role in protecting high-density lipoprotein (HDL) under oxidative stress. Different to the report by Patel and Mishra (2012), which indicated that the magnoflorine from Tinospora cordifolia stem inhibited α -glucosidase ability, the α-glucosidase inhibitory in this study was weak by a in vitro test (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Hung et al (2007) also have reported that, magnoflorine played a role in protecting high-density lipoprotein (HDL) under oxidative stress. Different to the report by Patel and Mishra (2012), which indicated that the magnoflorine from Tinospora cordifolia stem inhibited α -glucosidase ability, the α-glucosidase inhibitory in this study was weak by a in vitro test (data not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…The antioxidant activity of different structural feature and physicochemical properties of the magnoflorine have been test in inhibit free radical, peroxidation of dioleoyl phosphatidylcholine, and liposomes (Hung et al, 2007). Magnoflorine also has been reported to have the effect on inhibiting α-glucosidase in vitro and in vivo (Patel and Mishra, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Banyak penelitian telah membuktikan bahwa senyawa fitokimia memiliki kemampuan untuk menghambat kerja enzim alfa glukosidase, seperti senyawa dari golongan alkaloid (Patel et al 2012), triterpenes (Lai et al 2012), dan flavonoid (Wang et al 2010 a ) Penghambatan aktivitas alfa glukosidase oleh berbagai senyawa fenolik juga telah banyak dijelaskan dalam literatur, dimana antara lain disebutkan bahwa alfa glukosidase secara efektif dihambat oleh flavonol (Lee et al 2008), luteolin, myricetin, dan quercetin (Tadera et al 2006). Dengan demikian kemampuan aktivitas inhibitor alfa glukosidase yang dimiliki oleh ekstrak umbi bawang dayak tidak lepas dari kerja senyawa fitokimia yang dikandungnya.…”
Section: Penghambatan Aktivitas Enzim Alfa Glukosidaseunclassified
“…To date, a number of natural compounds that act as α-glucosidase inhibitors have been found in food (Peyrieras et al, 1983;Patel and Mishra, 2012), and many researches have elucidated the preventive effects of food ingredients on hyperglycemia (Shipra et al, 2010;Oe and Ozaki, 2008). Therefore, the identification of natural α-glucosidase inhibitors in food materials is of value in the development of new functional foods for the prevention of diabetes development and to reduce its incidence.…”
Section: Introductionmentioning
confidence: 99%